2022
DOI: 10.3389/fnagi.2022.872134
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Central and Peripheral Immune Systems in Neurodegenerative Diseases

Abstract: For decades, it has been widely believed that the blood–brain barrier (BBB) provides an immune privileged environment in the central nervous system (CNS) by blocking peripheral immune cells and humoral immune factors. This view has been revised in recent years, with increasing evidence revealing that the peripheral immune system plays a critical role in regulating CNS homeostasis and disease. Neurodegenerative diseases are characterized by progressive dysfunction and the loss of neurons in the CNS. An increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 222 publications
0
25
0
Order By: Relevance
“…Previous study has shown that SARS-CoV-2 could infect neural tissues and cause significant neuronal death based on experimental evidence in human brain organoids, mice with over-expressing ACE2, and autopsies from patients who died of COVID-19 [ 10 ]. Meanwhile, the innate immune responses and cytokine storm triggered by COVID-19 might also promote the development or progression of neurodegeneration [ 11 ]. Peripherally released cytokines could cross the blood-brain barrier, thus causing direct neurotoxicity and contributing to the activation of microglia and astrocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown that SARS-CoV-2 could infect neural tissues and cause significant neuronal death based on experimental evidence in human brain organoids, mice with over-expressing ACE2, and autopsies from patients who died of COVID-19 [ 10 ]. Meanwhile, the innate immune responses and cytokine storm triggered by COVID-19 might also promote the development or progression of neurodegeneration [ 11 ]. Peripherally released cytokines could cross the blood-brain barrier, thus causing direct neurotoxicity and contributing to the activation of microglia and astrocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy CNS, the CD4 + T cells, although at a low number, are crucial for the maturity and function of microglia, affecting memory, behavior, and other functions of the brain 40 . Under pathological conditions, peripheral CD4 + T cells can be recruited by activated glia cells, infiltrated inflammation cells, injured neurons, or endothelial cells and produce cytokines to mediate CNS inflammation after re‐activation by MHCII + antigen‐presenting cells (APCs) 41 . Since irradiation promotes the release of autoantigens or new antigens, it is rational that brain irradiation induces unknown antigens that can be recognized by APCs, which further triggers the neuroimmunology processes as previously mentioned 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that the peripheral immune system plays an essential role in the regulation of CNS homeostasis and diseases ( 20 ). Brain infiltration of the NK cells has been widely observed in neurodegenerative disorders, including AD and PD, and may play diverse roles under different conditions ( 14 , 17 ).…”
Section: Discussionmentioning
confidence: 99%